The Challenges of Islamic Microfinance (Indonesia Evidence) - Prastowo, Lucky Nugroho (European Journal of Islamic Finance, 2015)
Microfinance institutions and Islamic microfinance institutions that do not have a body would be transformed into cooperatives (Coop) or shareholder firms (SHFs) company under the act No.1 of 2013 (UU No.1 Tahun 2013) regarding microfinance institutions. One of Islamic microfinance institutions for being Baitul Mal Wa Tamwil (BMT) that currently a majority of non-governmental organizations are required to transform to become more professional, and should be answer the challenge in the future. In this literature review there are some challenges for BMT to be transformed and can be exist in future. The challenges of BMT, are what the microfinance market that also relevant to the Islamic perspective will be needed in future. This literature review is limited by three questions, (i) What is the purpose of BMT?, (ii) What are the challenges of BMT in the future?, (iii) What are the advantages BMT incorporated in?